The Effect of Teacher Competence on Organizational Citizenship Behavior: The Mediating Role of Subjective Well-Being - Ahmad Afandi; Hasan Baharun (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine the effect of teacher competence on organizational citizenship behavior (OCB) with subjective well-being as an intervening variable, in order to contribute to improving the quality of private Tsanawiyah Madrasas, particularly in Lumajang Regency. This research employed a quantitative approach with an explanatory design to analyze causal relationships among variables through hypothesis testing. Data were collected using structured questionnaires distributed to 101 certified teachers. The data were then analyzed using statistical techniques to determine direct and indirect effects between variables. The results indicate that teacher competence does not have a direct significant effect on organizational citizenship behavior. However, teacher competence has a strong positive effect on subjective well-being, accounting for 78.9% of the variance. Furthermore, subjective well-being significantly influences organizational citizenship behavior, contributing 61.7%. Importantly, teacher competence indirectly affects organizational citizenship behavior through subjective well-being, with an effect size of 48.7%, indicating the mediating role of subjective well-being. In conclusion, subjective well-being plays a crucial mediating role in strengthening the relationship between teacher competence and organizational citizenship behavior. These findings imply that improving teacher competence alone is insufficient to enhance OCB unless it is accompanied by efforts to improve teachers’ psychological well-being. Therefore, educational stakeholders, particularly in private madrasas, should design policies and programs that simultaneously enhance professional competence and promote teachers’ well-being to achieve optimal organizational performance.